Múltiplas vozes, um narrador: o jogo narrativo em A tirania do amor de Cristovão Tezza - MARQUES, Jéssica Souza Pereira (2024)
This work aimed to study the role of the narrator and his progress in “A Tirania do Amor” (2018), a Cristóvão Tezza’s contemporary book. In this work, we assume the narrator, in contemporary Brazilian fiction, has a wide range of features, according the novel he’s conducting, which is possible to see a kind of game, a contest of fictional voices that seek for legitimacy in story. So, the narrator, using a lot of voices and perspectives, performs an essential role in narrative configuration and understanding of the characters. We suggest the storytelling techniques and articulating voices are essential to understand the complexity of the plots and the deepness of the protagonists, which justifies this study. During the research, we’ll study how the contemporary narrator conducts the diegesis, emphasizing the polyphony and the dialog of voices which interweave and influences the narrative. So, the work engages the contemporary narrator studies, his peculiarities and the roles that assumes before Contemporary Brazilian Literature. We’ll investigate also the aspects of point of views and voice in the book, study object, emphasizing the multiplicity of voices of its fictional subjects in the narrative since the building of these voices and its Tezza’s work connection will be essential to understand deepness and story complexity. In these terms, we’ll analyze the narrative game made by the narrator, his articulation in studied book, which we seek the thinking about the narrator’s commitment and his influence about the reader. In conclusion, this work seeks the interactions already quoted, while thinks about contemporary literature trends. As theoretical support we use specially Afrânio Coutinho (2015), Beatriz Resende (2008), Karl Schollhammer (2009), Jaime Ginzburb (2012), Regina Dalcastagnè (2012), Wayne C. Booth (2022), Gerard Genette (1979), Ligia Leite (1994), Paul Ricoeur (2010), Mikhail Bakhtin (2002), Luís Alberto Santos and Silvana Oliveira (2001) who confirm the understanding about means and modes of building of the contemporary narrator.